Pengaruh Pelayanan Penyelenggaraan Perjalanan terhadap Tingkat Kepuasan Konsumen : Studi Kasus PT Wirakusuma Wahanakencana Tours And Travel - Prabowo, Agung (Jurnal Ilmiah Ranggagading (JIR), 2005)
The results of research indicates that if the value of a and b is unveiled it is put into correlation regression know as r. The value of r is 0.59. After the value of r is obtained it is inserted in the formula of determination coefficient the result of which is 34.81%, while the rest/balance amounting to 65.19% is influenced by other factors. This indicates that there is mediocre influence between tour organizing service and consumers satisfaction. For the sake of hypotheses the writer uses t trial which results 5.17. The result is compared to the r table value which is 0.279. So it can be concluded that ha is accepted and ho is refused. This indicates that the service influences the satisfaction of the consumers. Key words: Tour Organizing Servicea; Costumer Satisfaction